2009
DOI: 10.1111/j.1439-0531.2007.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Plasma Pregnancy‐associated Glycoprotein 1 Concentrations Throughout Gestation in High‐producing Dairy Cows

Abstract: This study was designed to establish the factors, if any, which could affect plasma pregnancy-associated glycoprotein-1 (PAG-1) expression in a study population of 87 pregnant, high-producing dairy cows. The factors examined were: semen providing breed (Holstein-Friesian vs Limousin), outcome of gestation (male vs female newborn, and singleton vs twin pregnancies), lactation number, milk production at pregnancy diagnosis, plasma progesterone concentration, season of gestation (warm period, March-November vs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
5
22
0
1
Order By: Relevance
“…Pure-breed beef and dairy cow gestations (H-H and RG-RG) showed lower PAG-1 concentrations compared with the concentrations observed in the crossbreed pregnancies, H-L (AI), and H-RG-ET (embryo transfer), in agreement with findings reported in cattle [22,37] and goats [38]. These findings suggest that the higher PAG-1 concentrations in crossbreed pregnancies reduce exposure of the 3.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Pure-breed beef and dairy cow gestations (H-H and RG-RG) showed lower PAG-1 concentrations compared with the concentrations observed in the crossbreed pregnancies, H-L (AI), and H-RG-ET (embryo transfer), in agreement with findings reported in cattle [22,37] and goats [38]. These findings suggest that the higher PAG-1 concentrations in crossbreed pregnancies reduce exposure of the 3.…”
Section: Discussionsupporting
confidence: 93%
“…It has also been established that beef cows or cows with a crossbreed pregnancy, especially for a greater maternal-paternal genetic distance, show a reduced risk of abortion when naturally infected compared with pure-breed Holstein Friesian (HF) pregnancies [17][18][19][20][21]. Compared with purebreed HF pregnancies, crossbreed pregnancies feature greater PAG-1 concentrations [22,23], suggesting a protective role of PAG-1 against rejection of the fetus. The reason why crossbreed and beef cow pregnancies in N caninum-infected cows show this dramatically lower abortion risk remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, during the warm months, the conception rate decreases (López-Gatius 2003;López-Gatius et al 2005;García-Ispierto et al 2007), besides an increase in postpartum interactions among reproductive disorders such as lactation number, placenta retention, metritis, ovarian cysts and days open (Labèrnia et al 1998), and there is a higher incidence of early fetal loss (López-Gatius et al 2004a, b, c;Bech-Sàbat et al 2008). In (10) T Temperature (°C), RH relative humidity (%), THI temperature-humidity index a Variations of the temperature or THI values for mean daily values 1.2 times higher than the mean daily values of the 10 previous days b Fetal loss referred to cows inseminated every month a recent study (Serrano et al 2009) analyzing conceptusmaternal interactions by measuring plasma pregnancy associated glycoprotein (PAGs) concentrations, the development of a healthy placenta was strongly linked to gestations occurring from December to February. Plasma PAGs levels have been used as markers of placental/fetal well-being , and conception during the remaining months (March-November) was related to decreasing PAGs plasma concentrations throughout the gestation period (Serrano et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In (10) T Temperature (°C), RH relative humidity (%), THI temperature-humidity index a Variations of the temperature or THI values for mean daily values 1.2 times higher than the mean daily values of the 10 previous days b Fetal loss referred to cows inseminated every month a recent study (Serrano et al 2009) analyzing conceptusmaternal interactions by measuring plasma pregnancy associated glycoprotein (PAGs) concentrations, the development of a healthy placenta was strongly linked to gestations occurring from December to February. Plasma PAGs levels have been used as markers of placental/fetal well-being , and conception during the remaining months (March-November) was related to decreasing PAGs plasma concentrations throughout the gestation period (Serrano et al 2009). With the above results in mind, as episodes of maximum THI increase were only recorded during the December-February period, it is especially relevant the fact that these episodes occurring during the embryonic period were related to subsequent fetal loss.…”
Section: Discussionmentioning
confidence: 99%
“…) and higher plasma concentrations of PAG‐1 have been observed in cross‐breed dairy cattle gestations compared to pure‐breed gestations (Serrano et al. ). In a previous study, PAG‐1 concentrations were found to be unaffected by persistent N. caninum infection in non‐aborting dairy cows, but were low or undetectable in cows with a mummified foetus (López‐Gatius et al.…”
Section: Introductionmentioning
confidence: 99%